Human equilibrative nucleoside transporter 1 expression analysed by the clone SP 120 rabbit antibody is not predictive in patients with pancreatic cancer treated with adjuvant gemcitabine – Results from the CONKO-001 trial. Issue 12 (August 2015) - Sinn, M.; Riess, H.; Sinn, B.V.; Stieler, J.M.; Pelzer, U.; Striefler, J.K.; Oettle, H.; Bahra, M.; Denkert, C.; Bläker, H.; Lohneis, P.
Abstract Background High expression of human equilibrative nucleoside transporter 1 (hENT1) is considered to predict survival in patients treated with adjuvant gemcitabine for pancreatic cancer. A standard evaluation system for immunohistochemical analysis (antibody, scoring system) has not yet been established. Methods CONKO-001, a prospective randomised phase III study investigated the role of adjuvant gemcitabine (gem) as compared to observation (obs). Tumour samples of 156 patients were analysed by immunohistochemistry with the rabbit monoclonal antibody SP120 (Ventana Medical Systems) for expression of hENT1. Kaplan–Meier analyses for median disease-free survival (DFS) and overall survival (OS) were performed in dependence of hENT1 expression measured analogously to Farrell et al. 2009 and Poplin et al. 2013. Results For the 88 gem and 68 obs patients, median DFS/OS was 12.9/22.7 months and 6.2/19.1 months. High hENT1 expression was not associated with improved median DFS (Farrell: no hENT1 22.2 months, low hENT1 13.7 months, high hENT1 12.1 months, p = 0.248; Poplin: low hENT1 13.2 months versus high hENT1 11.5 months, p = 0.5) or median OS (Farrell: no hENT1 21.7 months, low hENT1 24.7 months, high hENT1 19.5, p = 0.571; Poplin: low hENT1 24.4 months versus high hENT1 19.7 months, p = 0.92;) in the gem group or in the obs group (median DFS Farrell: no hENT1 5.1 months, low hENT1 6.2 months, high hENT1 7.5 months, p = 0.375; Poplin: low hENT1 6.2 months versus high hENT1 5.9 months, p = 0.83; median OS Farrell: no hENT1 20.2 months, low hENT1 17.7 months, high HENT1 19.1 months, p = 0.738; Poplin: low hENT1 17.7 months versus high hENT1 20.4 months, p = 0.65) measured by the Farrell or Poplin Score. Conclusions We cannot confirm a predictive role of hENT1 measured by the clone SP120 rabbit antibody in our study population. Reproducible standard procedures are urgently needed prior to the implementation or exclusion of hENT1 as a predictive biomarker in the treatment of pancreatic cancer. Trial registration ISRCTN34802808.